Vol 2 no 2 Tahun 2024 SIMPANAN QURBAN DALAM PERSPEKTIF EKONOMI SYARIAH : (STUDI KASUS KSPPS BISMILLAH CABANG NGADIREJO KABUPATEN TEMANGGUNG ) - annuroin, nur muh (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2024)
Qurban Savings is a medium for storing funds in the form of savings intended for people to plan Qurbani worship, with flexible deposits. This product is a savings product with a mudharabah contract, namely members as shohibulmaal (fund owners) while KSPPS Bismillah as mudharib (implementer/business manager), for this collaboration applies a profit-sharing system with a ratio that has been agreed in advance. The purpose of this study is to find out the practice of Qurban Savings and the analysis of Qurban Savings products reviewed from the perspective of sharia business at KSPPS Bismillah Ngadirejo Branch, Temanggung Regency. The method used in this thesis is a qualitative method. The data collection can be done by an interview system with the Manager, Employees, Customers of KSPPS Bismillah Ngadirejo Branch as well as direct observation of certain objects that are the focus of the research and record everything related to Qurban Deposits at KSPPS Bismillah Ngadirejo Branch, Temanggung Regency as well as documentation related to this research. From the results of the study, it can be concluded that, the practice of the Qurban Savings product of KSPPS Bismillah Ngadirejo Branch, every member who wants to keep qurbani savings, is required to become a member, pay a principal deposit of Rp. 50.000,00, attach a photocopy of a valid ID card and pay an administrative fee of Rp. 5.000,00. For the withdrawal of Qurban Savings at least one month before Eid al-Adha, the initial deposit is at least Rp. 10.000,00 and the next deposit is at least Rp 5.000,00. Funds for this deposit product can be done in cash or book transfer. Withdrawals from deposits can be made at all KSPPS Bismillah branch offices by bringing a passbook and an original identity card. Withdrawal of deposits cannot be represented, and if it is urgent, a sufficient stamped power of attorney from the account owner must be attached accompanied by proof of original identity from the account owner accompanied by proof of original identity from the owner and authorized recipients. The minimum balance after the deposit is taken Rp 10.000,00 and the customer gets the result according to the calculation of the daily average balance. Profit sharing is calculated at the end of the month and added to the customer's account at the end of the month, with a ratio of 65% for KSPPS Bismillah and 35% for customers. If the customer wants to close the book or close the account, an administration fee of Rp10.000,00 will be charged to the customer concerned. Qurban savings products at KSPPS Bismillah Ngadirejo Branch, Temanggung Regency If reviewed with DSN-MUI Fatwa Number 02/DSNMUI/IV/2000 concerning savings, the implementation of the practice of Qurban Savings products at KSPPS Bismillah Ngadirejo Branch, Temanggung Regency is fully in accordance with Islamic provisions.